A students' challenge for the estimation of the maximum compressive load of masonry prisms - Ramos, Luís F. (2016)
The paper presents the "IMC Students' Challenge" competition held in 2014, during the 9th International Masonry Conference, in Guimaraes. The objective of the competition was to predict the maximum compressive load of two masonry prisms built of solid bricks, and of hollow blocks, with mortar joints. To increase the complexity of the problem, all prisms were tested under eccentric load. The students, who enthusiastically participated in the final laboratory tests, presented different approaches to estimate the maximum eccentric compressive force on masonry prisms. The challenge was a great experience, not only for students and - conference participants, but also for sponsors and organizers.